2012
DOI: 10.1074/jbc.m112.355099
|View full text |Cite
|
Sign up to set email alerts
|

rRNA Genes Are Not Fully Activated in Mouse Somatic Cell Nuclear Transfer Embryos

Abstract: Background: The nucleolus always shows delayed development and malfunction in somatic cell nuclear transfer (NT) embryos. Results: NT embryos showed low rDNA activity and developmental competence when donor cells with low rDNA activity were used. Conclusion: rDNA reprogramming efficiency in NT embryos was determined by the rDNA activity in donor cells from which they derived. Significance: Developmental potential of NT embryos with rDNA activity in the donor cells was correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…Lastly, we have verified that the synthesis of rRNAs is not affected in spermatid-derived embryos. Indeed, in mouse, defect in rRNA synthesis has been proposed to explain the developmental defect of nuclear transfer embryos (Suzuki et al 2007;Zheng et al 2012) and could explain the difference in the bulk of RNA synthesis observed between sperm-and spermatid-derived embryos (Bui et al 2011). We observed that newly synthesized 18S and 28S rRNAs are equally well produced in sperm-and spermatid-derived embryos (Supplemental Fig.…”
Section: Developmentally Important Genes Are Misregulated In Spermatimentioning
confidence: 52%
See 2 more Smart Citations
“…Lastly, we have verified that the synthesis of rRNAs is not affected in spermatid-derived embryos. Indeed, in mouse, defect in rRNA synthesis has been proposed to explain the developmental defect of nuclear transfer embryos (Suzuki et al 2007;Zheng et al 2012) and could explain the difference in the bulk of RNA synthesis observed between sperm-and spermatid-derived embryos (Bui et al 2011). We observed that newly synthesized 18S and 28S rRNAs are equally well produced in sperm-and spermatid-derived embryos (Supplemental Fig.…”
Section: Developmentally Important Genes Are Misregulated In Spermatimentioning
confidence: 52%
“…Several hypotheses were proposed to explain the nature of this programming, including the idea that sperm is programmed for efficient replication after fertilization (Lemaitre et al 2005) or for supporting proper embryonic transcription (Suzuki et al 2007;Hammoud et al 2009;Zheng et al 2012). The latter hypothesis was proposed following the observation that promoters of developmentally important genes escape global replacement of histones by protamines in mature sperm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ICSI was carried out with a piezo-driven unit using a previously described method (Tesarik et al, 2002;Zheng et al, 2012), except that our experiment was performed at room temperature in HEPES-CZB medium containing 5 g/ml cytochalasin B (Sigma). Whole spermatozoon were injected into oocytes.…”
Section: Mouse Oocyte Collection Ivf Icsi and Embryo Culturementioning
confidence: 99%
“…Microarray analysis of 2-cell mouse embryos has revealed that more than 2000 mRNAs are misregulated in NT embryos compared to fertilised embryos [152]. Transcription by RNA polymerase I is also disturbed in cloned embryos around this stage [139, 153]. This early abnormal gene expression can be rescued by treatment with histone deacetylase inhibitors [135, 139], suggesting that abnormal gene expression in early embryos is at least partially due to the somatic epigenome, which is not adequate to support the embryonic gene expression program.…”
Section: Abnormalities In Cloned Embryos In Relation To Somatic Cell mentioning
confidence: 99%